Njáls saga : La saga di Njáll : dal codice Reykjavík, Safn Árna Magnússonar, AM 133 fol - A. Meregalli (Novus Press, 2018)
This is an Italian translation of an excerpt from "Njáls saga" (chapters 9-11) edited on facing pages by Odd Einar Haugen from the manuscript Reykjavik, Arnamagnaean Collection, AM 133 fol. This is part of a volume on the Nordic languages in the Middle Ages.